2014
DOI: 10.1055/s-0034-1381955
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet Inhibition in Microvascular Surgery

Abstract: Thrombosis remains a significant complication of microvascular free tissue transfer. Recent discoveries in the field of vascular biology have led to a greater understanding of thrombogenesis and the pivotal role that platelets play in the formation of a clot. However, current antithrombotic strategies in the clinical practice of free tissue transfer have not typically focused on platelet inhibition. Decades of cardiovascular clinical trials have delineated the essential role of platelet inhibitor therapy in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Recent studies have suggested that heparin improves results and that aspirin could reduce the thrombotic properties of platelets (Iamaguchi et al, ). In a 2014 case series by Cho et al () it was demonstrated that two free flap procedures requiring salvage were successfully managed with intravenous eptifibatide (Cho et al, ). Another study by Natelson () generated the following recommendations: combination of antimetabolite treatment (cytarabine or hydroxyurea), anagrelide (Phosphodiesterase (PDE) inhibitor that antagonizes maturation of platelets), and/or plateletpheresis to reduce platelet count to <400,000 prior to any interventional vascular surgical procedure (Natelson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that heparin improves results and that aspirin could reduce the thrombotic properties of platelets (Iamaguchi et al, ). In a 2014 case series by Cho et al () it was demonstrated that two free flap procedures requiring salvage were successfully managed with intravenous eptifibatide (Cho et al, ). Another study by Natelson () generated the following recommendations: combination of antimetabolite treatment (cytarabine or hydroxyurea), anagrelide (Phosphodiesterase (PDE) inhibitor that antagonizes maturation of platelets), and/or plateletpheresis to reduce platelet count to <400,000 prior to any interventional vascular surgical procedure (Natelson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that heparin improves results and that aspirin could reduce the thrombotic properties of platelets (Iamaguchi et al, 2018). In a 2014 case series by Cho et al (2014) it was demonstrated that two free flap procedures requiring salvage were successfully managed with intravenous eptifibatide (Cho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical experience, preoperative thrombocytosis in the setting of severe tissue damage should alert the surgeon to a greater risk of microvascular complications. Future studies are warranted to determine whether high‐risk patients undergoing free flap reconstruction stand to benefit from targeted antiplatelet therapies …”
Section: Discussionmentioning
confidence: 99%
“…[41,56] This combination of fibrin production and platelet activation/aggregation are central events in arterial and venous thrombosis by contributing to intimal hyperplasia, smooth muscle cell degeneration, and formation of intraluminal thrombi at the anastomotic site. [41,5759,40,60] The role of tamoxifen in increasing platelet activation and aggregation is considered the primary mechanism by which it induces a prothrombotic environment in patients with breast cancer. Recently, investigators demonstrated tamoxifen promotes calcium entry into platelets, which is critical to platelet activation and aggregation, and may lead to prothrombotic platelet phenotypes in breast cancer patients on hormone therapy.…”
Section: Discussionmentioning
confidence: 99%